The concentration of heavy metal content at different operational zone on peat soil at Felcra Sri Mendapat / Mohamad Nazmi Mohamad Sharif - Mohamad Sharif, Mohamad Nazmi (Faculty of Plantation and Agrotechnology, 2015)
Heavy metals are bioaccumulation and non-degradable elements in the soil. The contamination by heavy metals in soil is one of the important issues and requires attention because heavy metals above the maximum allowable concentration will threatened to both plants and living things. I was therefore of interest to conduct a study regarding the concentration of heavy metals on peat soil at FELCRA Sri Mendapat. The soil was also analyzed for its properties such as pH and moisture. Besides that, the soil samples were collected at different operational zones such as pesticide area, frond heap, weeded circle and harvesting path. Heavy metals for which these samples were analyzed were zinc,chromium were recorded as exceeded the maximum allowable concentration (MAC) set by World Health Organization (WHO) while zinc was recorded below the MAC. The pH of all soil samples were recorded in acid condition and a range within 3-5. Meanwhile the soil moisture for all samples was recorded in a range within 150-260 mBar. The moisture of the soil is considered dry above than 230 mBar. Most of the operational zones are under normal moisture except the harvesting path zone which is above than 230 mBar. The relationship between soil pH and soil moisture have significant difference toward heavy metal concentration.